Prognosis criteria of gastroesophageal reflux disease treatment efficacy in school-age children - S.L. Nyankovskyy; M.I. Horodylovska (Zaslavsky O.Yu., 2018)
The important aspect of improving the treatment of children with gastroesophageal reflux disease (GERD) is its individualization. It is impossible without the development of predictors of the treatment efficacy. Outpatient treatment, endoscopic and morphological studies, common blood count and biochemical parameters have the highest prognostic value for the prediction of treatment efficacy in children with GERD. This prognostic algorithm has a high reliability (≥ 95 %) and makes it possible to predict the treatment efficacy for children with GERD. In case of an unfavorable prognosis, it is possible to personify the treatment by neutralizing controlled adverse prognostic factors of a particular patient.